Nucleophilic Degradation of Fenitrothion Insecticide and Performance of Nucleophiles: A Computational Study - Mandal, Debasish; Mondal, Bhaskar; Das, Abhijit K (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2012)
Ab initio and density functional theory (DFT) calculations have been performed to understand the destruction chemistry of an important organophosphorus insecticide O,O-dimethyl O-(3-methyl-4-nitrophenyl) phosphorothioate, fenitrothion (FN), toward nucleophilic attack. Breaking of the P–OAr linkages through nucleophilic attack is considered to be the major degradation pathway for FN. One simple nucleophile, hydroxide (OH–), and two different α-nucleophiles, hydroperoxide (OOH–) and hydroxylamine anion (NH2O–), have been considered for this study. Nucleophilic attack at the two different centers, SN2@P and SN2@C, has been monitored, and the computed reaction energetics confirms that the SN2@P reactions are favorable over the SN2@C reactions for all the nucleophiles. All electronic structure calculations for the reaction are performed at DFT-B3LYP/6-31+G(d) level of theory followed by a refinement of energy at ab initio MP2/6-311++G(2d,2p) level. The effect of aqueous polarization on both the SN2 reactions is taken into account employing the conductor-like screening model (COSMO) as well as polarization continuum model (PCM) at B3LYP/6-31+G(d) level of theory. Relative performance of the two α-nucleophiles, OOH– and NH2O–, at the P center has further been clarified using natural bond orbital (NBO), conceptual DFT, and atoms in molecules (AIM) approaches. The strength of the intermolecular hydrogen bonding in the transition states and topological properties of the electron density distribution for −X–H···S (X = O, N) intermolecular hydrogen bonds are the subject of NBO and AIM analysis, respectively. Our calculated reaction energetics and electronic properties suggest that the relative order of nucleophilicity for the nucleophiles is OOH– > NH2O– > OH– for the SN2@P, whereas for the SN2@C the order, which gets little altered, is NH2O– > OOH– > OH–.